Repurposed Analog of GLP-1 Ameliorates Hyperglycemia in Type 1 Diabetic Mice Through Pancreatic Cell Reprogramming - Villalba, Adrian; Rodriguez-Fernandez, Silvia; Perna-Barrull, David; Ampudia, Rosa-Maria; Gomez-Muñoz, Laia; Pujol-Autonell, Irma; Aguilera, Eva; Coma, Mireia; Cano-Sarabia, Mary; Vázquez, Federico; Verdaguer, Joan; Vives-Pi, Marta (Frontiers in Endocrinology, 2020)
Type 1 diabetes is an autoimmune disease caused by the destruction of the insulin-producing β-cells. An ideal immunotherapy should combine the blockade of the autoimmune response with the recovery of functional target cell mass. With the aim to develop new therapies for type 1 diabetes that could contribute to β-cell mass restoration, a drug repositioning analysis based on systems biology was performed to identify the β-cell regenerative potential of commercially-available compounds. Drug Repositioning is a strategy used for identifying new uses for approved drugs that are outside the scope of the medical indication. A list of 28 non-synonymous repurposed drug candidates was obtained, and 16 were selected as diabetes mellitus type 1 treatment candidates regarding pancreatic β-cell regeneration. Drugs with poor safety profile were further filtered out. Lastly, we selected liraglutide for its predictive efficacy values for neogenesis, transdifferentiation of α-cells and/or replication of pre-existing β-cells. Liraglutide is an analogue of glucagon-like peptide-1, a drug used in patients with type 2 diabetes. Liraglutide was tested in immunodeficient NOD-Scid IL2rg-/- (NSG) with type 1 diabetes. Liraglutide significantly improved blood glucose levels in diabetic NSG mice. During the treatment, a significant increase in -cell mass was observed, due to a boost in -cell number. Both parameters were reduced after withdrawal. Interestingly, islet bihormonal glucagon+insulin+ cells and insulin+ ductal cells arose during treatment. In vitro experiments showed an increase of insulin and glucagon gene expression in islets cultured with liraglutide in normoglycaemia conditions. These results point to β-cell replacement, including transdifferentiation and neogenesis as aiding factors, and support the role of liraglutide in β-cell mass restoration in type 1 diabetes. Understanding the mechanism of action of this drug could have potential clinical relevance in this autoimmune disease.